2019
DOI: 10.24843/ejmunud.2019.v08.i11.p09
|View full text |Cite
|
Sign up to set email alerts
|

Peran Brand Awareness Memediasi Pengaruh Advertising Terhadap Keputusan Pembelian

Abstract: The purpose of this study was to examine the role of brand awareness in mediating the influence of advertising on purchasing decisions in the Tokopedia application in Denpasar City. The variables examined in this study were advertising variables, brand awareness and purchasing decisions. This research was conducted in Denpasar City and the population in this study were people who had already made transactions at Tokopedia in Denpasar City. The sample in this study consisted of 120 respondents. This study uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
0
6
0
4
Order By: Relevance
“…also found that Social Media Marketing has an effect on Brand Awareness via Facebook in the Mobile Services Sector in Egypt. In addition, Social Media Marketing affects Brand Awareness, it can be proven because it is supported by research that has previously been carried out by Endyana & Ardani (2019), showing the results of their research that Social Media Marketing has an influential and significant relationship with Brand Awareness.…”
Section: Relationship Between Social Media Marketing Brand Awareness ...mentioning
confidence: 74%
See 1 more Smart Citation
“…also found that Social Media Marketing has an effect on Brand Awareness via Facebook in the Mobile Services Sector in Egypt. In addition, Social Media Marketing affects Brand Awareness, it can be proven because it is supported by research that has previously been carried out by Endyana & Ardani (2019), showing the results of their research that Social Media Marketing has an influential and significant relationship with Brand Awareness.…”
Section: Relationship Between Social Media Marketing Brand Awareness ...mentioning
confidence: 74%
“…It is important if the customer has knowledge of the brand, because if the customer does not know the use of the product, the customer will not buy it either (Herdana, 2015). According to Endyana & Ardani (2019), consumer recall of the brand from the lowest level to the highest level There are four, namely: 1. Top of Mind.…”
Section: Brand Awarenessmentioning
confidence: 99%
“…The advertising variable in this study uses a measuring tool adapted from Endyana and Ardani (2019). Advertising is offering activities to a society orally or in writing (news) about a product, service, or idea.…”
Section: Measurementmentioning
confidence: 99%
“…Berdasarkan data dari Statista, kunjungan web e-commerce pada kuartal pertama di tahun 2020, Shopee berada pada posisi teratas yakni 71,53 juta klik per bulan, Tokopedia pada peringkat nomor dua yakni 69,8 juta klik per bulannya. Dikutip dari Endyana & Ardani (2019), "kemunculan dari banyak pesaing yang bergerak di bidang bisnis online menuntut Tokopedia menginovasi teknik pemasaran yang dilakukan" Inovasi pemasaran Tokopedia pada masa pasca covid-19 memilki peluang besar dalam melaksanakan aktivitas pemasaran. Keberadaan Tokopedia menjadi sumber berbagai informasi diharapkan mampu merubah perilaku masyarakat.…”
Section: Gambar 2 Top 10 E-commerce DI Indonesia Kuartal I 2020unclassified